Answer:
A. x=6 B. x=4.5 C. x-35 D. x=13
Step-by-step explanation:
For A and B, divide the numbers you have. For C and D, multiply the numbers you have.
Answer:
(x -2)^2 + (y-6)^2 = 16
Step-by-step explanation:
The equation of a circle is of the form
(x-h)^2 + (y-k)^2 = r^2
where (h,k) is the center and r is the radius
(x- 2)^2 + (y-6)^2 = 4^2
(x -2)^2 + (y-6)^2 = 16
Use the lengths of corresponding sides
so answer is 16:40 which simplifies to 2:5.
You would change the whole number to a fraction by putting it over 1 and make the mixed number an improper fraction by multiplying the whole number part of the mixed number by the denominator and then and the numerator